Leptin Deficiency Contributes to the Pathogenesis of Alcoholic Fatty Liver Disease in Mice - Tan, Xiaobing (American Society for Investigative Pathology, 2012)
White adipose tissue (WAT) secretes adipokines, which critically regulate lipid metabolism. The present study investigated the effects of alcohol on adipokines and the mechanistic link between adipokine dysregulation and alcoholic fatty liver disease. Mice were fed alcohol for 2, 4, or 8 weeks to document changes in adipokines over time. Alcohol exposure reduced WAT mass and body weight in association with hepatic lipid accumulation. The plasma adiponectin concentration was increased at 2 weeks, but declined to normal at 4 and 8 weeks. Alcohol exposure suppressed leptin gene expression in WAT and reduced the plasma leptin concentration at all times measured. There is a highly positive correlation between plasma leptin concentration and WAT mass or body weight. To determine whether leptin deficiency mediates alcohol-induced hepatic lipid dyshomeostasis, mice were fed alcohol for 8 weeks with or without leptin administration for the last 2 weeks. Leptin administration normalized the plasma leptin concentration and reversed alcoholic fatty liver. Alcohol-perturbed genes involved in fatty acid β-oxidation, very low-density lipoprotein secretion, and transcriptional regulation were attenuated by leptin. Leptin also normalized alcohol-reduced phosphorylation levels of signal transducer Stat3 and adenosine monophosphate–activated protein kinase. These data demonstrated for the first time that leptin deficiency in association with WAT mass reduction contributes to the pathogenesis of alcoholic fatty liver disease.